Assessment of fuel cell studies with particle image velocimetry applications: A key review. (18th August 2021) - Yasar, Onur; Ozbek, Emre; Ekici, Selcuk; Yalcin, Enver; Midilli, Adnan; Karakoc, T. Hikmet
Abstract: Fuel cells are considered to be a promising system that is utilized in several applications and in various sectors. Particle image velocimetry is extremely practicable for the exploration of the flow field inside fuel cells and channels. This paper reviews fuel cell studies focusing on the particle image velocimetry technique in the open literature. In this regard, state-of-the-art and comparative evaluation have been investigated and are discussed. Additionally, challenges, opportunities and future direction have been studied in terms of fuel cell type, size, voltage value, current value, power output capacity, and CFD applications. It is concluded that the growing demand on fuel cells will increase system design, performance improvement and cost benefit efforts affected by the flow and design parameters and characteristics which are other important issues that could be covered using PIV methods in the future. Moreover, this review paper is expected to be a better guide for researchers, policy makers and technologists working on potential commercial applications of fuel cells in mobile and stationary platforms. Highlights: This work reviews fuel cell studies including the particle image velocimetry technique in the open literature. The state of the art and comparative evaluation of the works done in the literature investigate and discuss in detail. This paper aims to be a guideline for researchers and policymakers working on fuel cell technologies.